Profits realised beyond a ceiling being exempted from sharing in joint equity based facilities of Islamic banks - Sadique, Muhammad Abdurrahman (Zes Rokman Resources, 2018)
Customarily, joint equity ventures embarked on by Islamic banks define the profit shares accruing to the partners as a ratio of the total profit realisable through the venture. This is due to the fundamental principle that profit division should necessarily be based on a stipulated ratio. However, Islamic banks are noted stipulate in some equity partnership contracts that profits realised in excess of an agreed level should accrue to one partner, and will not be subject to division based on the ratio. The paper scrutinises the possibility of limiting the operation of the profit sharing ratio up to a pre-defined ceiling, with reference to accepted sources of Islamic law. It argues that restricting the application of the ratio to a stipulated level of profits defeats the objectives of equity financing. This would enable a partner to claim unlimited profits while the profit share of the other is restricted to a maximum, thus curtailing the free operation the profit sharing mechanism.